In situ controlled synthesis of porous Fe–N–C materials from oily sludge by chlorinating calcination and their novel application in supercapacitors. Issue 12 (5th November 2020) - Zhou, Hanfeng; Deng, Zhibo; Liu, Tianbao; Liu, Tao; Zhang, Lijuan; Su, Xintai; Lin, Zhang
Abstract : Highlights: 1. A novel method was used to fabricate porous Fe–N–C materials from the oily sludge with excellent supercapacitors' performance. 2. The formation mechanism of porous Fe–N–C materials was studied systematically. Abstract : The science linking thermochemical conversion of large-scale industry oily sludge with applied materials has been improved in the last ten years. However, with the traditional converting methods it is hard to precisely control the composition and structure of oily sludge-based products during pyrolysis due to the complexity of the composition of the oily sludge. Here, a chlorinating calcination method using sodium chloride (NaCl) as a chlorinating salt and template was first developed to prepare porous Fe–N–C materials (FCN-500) through pyrolysis of oily sludge containing iron-bearing minerals and pyridine. The formation mechanism of FCN-500 was proposed, where iron ions (Fe 3+ ) from the inorganic component (anorthite) in the sludge were rapidly dissociated with the assistance of NaCl, followed by coordination with the organic component (pyridine nitrogen) in the oily sludge to form the pyridine nitrogen–iron ((C5 H6 N) n –Fe) complex, and then carbonization. As-obtained FCN-500 exhibited higher specific capacitance (286.3 F g −1 at a current density of 0.5 A g −1 ), enhanced energy density (33.5 W h kg −1 at a power density of 606.1 W kg −1 ) and more excellent stability and durability (more than 80.1% capacitance retention after 10 000 cycles) compared with two other electrodes. The reasonably better performance of the obtained FCN-500 in supercapacitors (SCs) is attributed to its large surface area, hierarchically porous channels, high conductivity, and unique Fe–N–C structure. Therefore, this work not only provides a feasible way to solve the bottleneck problem in sludge pyrolysis, but also provides a method to design large scale porous Fe–N–C materials for practical applications.